2019
DOI: 10.1016/j.gendis.2019.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Emerging roles of lncRNAs in the post-transcriptional regulation in cancer

Abstract: Accumulating evidence indicates that long non-coding RNAs (lncRNAs) can play a pivotal role in regulation of diverse cellular processes. In particular, lncRNAs can serve as master gene regulators at transcriptional and posttranscriptional levels, leading to tumorigenesis. In this review, we discuss latest developments in lncRNA-meditated gene expression at the post-transcriptional level, including gene splicing, mRNA stability, protein stability and nuclear trafficking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
133
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(134 citation statements)
references
References 91 publications
(139 reference statements)
1
133
0
Order By: Relevance
“…Although they are not translated into protein, lncRNAs can share similar characteristics and mechanisms found in messenger RNA (mRNA) such as alternative splicing and polyadenylation. LncRNAs exert their function as gene regulators by serving as signals, decoys, and scaffolds through a partnership with RNA binding proteins in ribonucleoprotein complexes [17].…”
mentioning
confidence: 99%
“…Although they are not translated into protein, lncRNAs can share similar characteristics and mechanisms found in messenger RNA (mRNA) such as alternative splicing and polyadenylation. LncRNAs exert their function as gene regulators by serving as signals, decoys, and scaffolds through a partnership with RNA binding proteins in ribonucleoprotein complexes [17].…”
mentioning
confidence: 99%
“…Due to the heterogeneity of tumors and the complexity of the tumor microenvironment, these molecules can play a carcinogenic or tumor suppressive role in the same tumor. There is evidence that lncRNAs can act as molecular scaffolds, sponges or coactivators in tumor scaffolds by interacting with DNA, RNA or proteins [5,31,32] . At present, increasing evidence has shown that the abnormally high expression of SNHG12 plays a carcinogenic role in various malignant tumors [10][11][12][13][14][15][16][17][18][19][26][27][28][29] .…”
Section: Discussionmentioning
confidence: 99%
“…It was gradually recognized that lncRNAs are involved in transcriptional and post-transcriptional regulation by recruiting transcription factors, remodeling chromatin, splicing pre-mRNA, and acting as molecular sponges and scaffolds in multifarious diseases and tumors. These molecules act as tumor promoters or tumor suppressors in the multistep development of human tumors [5][6][7] . In addition, lncRNAs can be present in many tissues and uids for a long time, and can be used as a biomarker for extensive screening of diseases [8] .…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, many nuclear lncRNAs have been reported to reside in condensates, named collectively "membraneless compartments" [4]. A notable example are paraspeckles which comprise the lncRNA NEAT1 and RNA-binding proteins (RBPs) that influence gene expression by post-transcriptional regulation of splicing and polyadenylation [5,6], as well as by interaction with the SWI/SNF complex that remodels nucleosomes [7]. Similarly, the lncRNA MALAT1, which also forms condensates, has been shown to regulate gene expression by interactions with splicing factors [8].…”
Section: Introductionmentioning
confidence: 99%